LIST OF CURRENTLY INCURABLE DISEASES - Yuldasheva Khusnora Khusinboy kizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines the category of currently incurable diseases through a clinically serious and analytically cautious lens. In medical usage, an incurable disease is not a condition for which nothing can be done; rather, it is a condition for which no definitive curative therapy has yet been established, even though symptom control, slowing of progression, life prolongation, and quality-of-life improvement may all be possible. The article focuses on six major examples that are widely recognized by authoritative health institutions as lacking a current cure: HIV infection, Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and type 1 diabetes.